2021
DOI: 10.3389/fnins.2021.756951
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Gut Microbiome and Predicted Functional Metabolic Effects in an Australian Parkinson’s Disease Cohort

Abstract: Background: There has been increasing recognition of the importance of the gut microbiome in Parkinson’s disease (PD), but the influence of geographic location has received little attention. The present study characterized the gut microbiota and associated changes in host metabolic pathways in an Australian cohort of people with PD (PwP).Methods: The study involved recruitment and assessment of 87 PwP from multiple Movement Disorders Clinics in Australia and 47 healthy controls. Illumina sequencing of the V3 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 80 publications
(85 reference statements)
1
13
1
Order By: Relevance
“…An increasing number of studies, mainly from Western Europe, China, Japan and the United States, have highlighted important patterns in the GM profiles of PD patients ( Gorecki et al, 2019 ; Elfil et al, 2020 ; Lubomski et al, 2020 ), with more than 110 differentially abundant taxa described from the level of phylum to ASV or species ( Boertien et al, 2019 ; Bullich et al, 2019 ; Lubomski et al, 2020 ; Wallen et al, 2020 ; Kenna et al, 2021 ; Romano et al, 2021 ). Although notable differences exist between the studies (study design, inclusion criteria, ages, gender proportions, disease durations, methodology, etc.…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of studies, mainly from Western Europe, China, Japan and the United States, have highlighted important patterns in the GM profiles of PD patients ( Gorecki et al, 2019 ; Elfil et al, 2020 ; Lubomski et al, 2020 ), with more than 110 differentially abundant taxa described from the level of phylum to ASV or species ( Boertien et al, 2019 ; Bullich et al, 2019 ; Lubomski et al, 2020 ; Wallen et al, 2020 ; Kenna et al, 2021 ; Romano et al, 2021 ). Although notable differences exist between the studies (study design, inclusion criteria, ages, gender proportions, disease durations, methodology, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, lower levels of butyrate are linked to postural instability, gait disorders, Movement Disorder Society-Sponsored Revision of the Unified Parkinson’s Disease Rating Scale (MDS-UPDRS) part III motor scores and depression among PD patients showing a reduced count of Faecalibacterium [ 59 , 60 , 61 , 62 , 63 ]. Other butyrate-producing taxa, such as Blautia , Caprococcus , Rosburia and Prevotella , also exert immunomodulatory activities and are reduced in PD patients compared to controls [ 50 , 60 , 64 , 65 , 66 ]. In line with these data, a study conducted in central China on 39 PD patients and their healthy spouses reported an inverse association between Prevotella abundance and disease severity, thus confirming the important role of inflammation in disease progression [ 64 ].…”
Section: Parkinson’s Disease and Gut Microbiota: Links And Mechanismsmentioning
confidence: 99%
“…There is evidence that GM composition changes according to ethnicity and geographic location [ 91 , 92 ]. Concerning PD, studies conducted on a population-specific cohort of patients shows the prominence of some geographic signatures, albeit on a similar background of bacterial dysbiosis [ 64 , 65 , 66 , 68 , 71 , 72 , 73 , 78 ]. For example, feces from Northern German PD patients showed increased abundance in the Barnesiellaceae family [ 72 ], while the genera Butyricicoccus and Clostridium XIVb were linked to a cognitive deficit in a Chinese PD cohort [ 73 ].…”
Section: Parkinson’s Disease and Gut Microbiota: Links And Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…The following supporting information can be downloaded at: , Table S1. Parkinson disease patients and healthy controls: research papers and their conclusions—full version (PD—patients with Parkinson’s disease, HC—healthy controls) [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 60 , 64 , 83 ].…”
mentioning
confidence: 99%